Gintonin, an exogenous ginseng-derived LPA receptor Iigand, promotes corneal wound healing - Kim, Hyeon-Joong; Kim, Joon Young; Lee, Byung-Hwan; Choi, Sun-Hye; Rhim, Hyewon; Kim, Hyoung-Chun; Ahn, Seoung-Yob; Jeong, Soon-Wuk; Jang, Minhee; Choy, Ik-Hyun; Nah, Seung-Yeol (대한수의학회, 2017)
Ginseng gintonin is an exogenous ligand of lysophosphatidic acid (LPA) receptors. Accumulating evidence shows LPAhelps in rapid recovery of corneal damage. The aim of this study was to evaluate the therapeutic efficacy of gintonin in a rabbit model of corneal damage. We investigated the signal transduction pathway of gintonin in human corneal epithelium (HCE) cells to elucidate the underlying molecular mechanism. We next evaluated the therapeutic effects of gintonin, using a rabbit model of corneal damage, by undertaking histochemical analysis. Treatment of gintonin to HCE cells induced transient increases of [Ca2+](i) in concentration-dependent and reversible manners. Gintonin-mediated mobilization of [Ca2+](i) was attenuated by LPA1/3 receptor antagonist Ki16425, phospholipase C inhibitor U73122, inositol 1,4,5-triphosphate receptor antagonist 2-APB, and intracellular Ca2+ chelator BAPTA-AM. Gintonin facilitated in vitro wound healing in a concentration-dependent manner. When applied as an eye-drop to rabbits with corneal damage, gintonin rapidly promoted recovery. Histochemical analysis showed gintonin decreased corneal apoptosis and increased corneal cell proliferation. We demonstrated that LPA receptor activation by gintonin is linked to in vitro and in vivo therapeutic effects against corneal damage. Gintonin can be applied as a clinical agent for the rapid healing of corneal damage.